Effect Of Selenium Pre-Treatment On Acrylamide Formation, Physicochemical And Sensorial Properties Of Roasted Coffee Via Conventional And Superheated Steam - Mahmoud, Alafeef Ahmad Kamal (2021)
Selenium is an essential micronutrient with significant antioxidant activity promising in mitigating the formation of acrylamide during high-temperature roasting. The study aimed to investigate the potential of organic selenium as an antioxidant additive in mitigating acrylamide formation during coffee roasting under conventional and superheated steam roasting, to study the selenium uptake by green coffee beans, and to evaluate the antioxidant activities, physicochemical properties, and sensory properties of the coffee beans enriched with selenium (Se-coffee).